2012
DOI: 10.1039/c2ob26103k
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of BACE1 inhibition of tripartite structures by modification of membrane anchors, spacers and pharmacophores – development of potential agents for the treatment of Alzheimer's disease

Abstract: Systematic variation of membrane anchor, spacer and pharmacophore building blocks leads to an optimisation of the inhibitory effect of tripartite structures towards BACE1-induced cleavage of the amyloid precursor protein (APP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…To increase the probability of our reported findings not being due to pharmacological side effects, we used two different substances (T GL-189 and DAPT) with two different mechanisms (inhibition of β-and g-secretase). It was described previously that the application of GL-189 as a tripartite substance (T GL-189 ) reduces unspecific side effects by directing the pharmacophore to the catalytic center of the βsecretase (31,32,36). The reported reduction of IL-6 and TNFα as well as the increased secretion of IL-10 are therefore very probable induced by the reduced production of Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase the probability of our reported findings not being due to pharmacological side effects, we used two different substances (T GL-189 and DAPT) with two different mechanisms (inhibition of β-and g-secretase). It was described previously that the application of GL-189 as a tripartite substance (T GL-189 ) reduces unspecific side effects by directing the pharmacophore to the catalytic center of the βsecretase (31,32,36). The reported reduction of IL-6 and TNFα as well as the increased secretion of IL-10 are therefore very probable induced by the reduced production of Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…APP processing was pharmacologically inhibited by adding 10 µM of the γ-secretase inhibitor N-[N-(3,5-Difluorophenacetyl)-L-alanyl]-S-phenylglycine-t-butyl-ester (DAPT, Sigma-Aldrich, Munich, Germany) or 500 nM of the tripartite β-secretase inhibitor T GL-189 (provided by Prof. Knoelker, Dresden Germany) when exchanging the medium on the 7th div. (Figure 1) (31,32) The applied concentration of the secretase inhibitors did not reduce the viability of the cells.…”
Section: Inhibition Of App Processingmentioning
confidence: 96%
See 1 more Smart Citation
“…17–20 Peterson’s group proposed and developed a synthetic receptors/antigen strategy by incorporating cholesterol or cholesterylamine as membrane anchors to improve transmembrane uptake. 2123 A tripartite strategy has also been successfully applied to design compounds that include a β-secretase inhibitor, a spacer and a raftophile; subsequent studies demonstrated theirs significantly improved efficacy both in vitro and in vivo for β-secretase inhibition, 18, 24–27 thus providing a critical proof of principle for development of such inhibitors. Recently, our group embarked on development of novel bivalent compounds as potential neuroprotectants for AD by linking a multifunctional “warhead” with a membrane anchor moiety via a spacer.…”
Section: Introductionmentioning
confidence: 99%
“…33 Our studies also reported that the spacer length between the warhead and the anchor is crucial to the observed protective activities, consistent with the results of the tripartite compounds. 24, 26 Specifically, the optimal spacer length ranges from 17 to 21 atoms in our models. 29, 31, 33 Notably, our studies suggested that the spacer length and the anchor moiety of the bivalent compounds may determine the sub-cellular localization of these bivalent compounds with different, yet overlapping, biological activities.…”
Section: Introductionmentioning
confidence: 99%